The TRAF1-C5 region on chromosome 9q33 is associated with multiple autoimmune diseases. Issue 4 (10th May 2009) - Kurreeman, Fina A S; Goulielmos, George N; Alizadeh, Behrooz Z; Rueda, Blanca; Houwing-Duistermaat, Jeanine; Sanchez, Elena; Bevova, Marianna; Radstake, Timothy R; Vonk, Madelon C; Galanakis, Emmanouil; Ortego, Norberto; Verduyn, Willem; et al.
Abstract : Objectives: The TRAF1-C5 locus has recently been identified as a genetic risk factor for rheumatoid arthritis (RA). Since genetic risk factors tend to overlap with several autoimmune diseases, a study was undertaken to investigate whether this region is associated with type 1 diabetes (TID), celiac disease (CD), systemic sclerosis (SSc) and systemic lupus erythematosus (SLE). Methods: The most consistently associated SNP, rs10818488, was genotyped in a total of 735 patients with T1D, 1049 with CD, 367 with SSc, 746 with SLE and 3494 ethnically- and geographically-matched healthy individuals. The replication sample set consisted of 99 patients with T1D, 272 with SLE and 482 healthy individuals from Crete. Results: A significant association was detected between the rs10818488 A allele and T1D (OR 1.14, p=0.027) and SLE (OR 1.16, p=0.016), which was replicated in 99 patients with T1D, 272 with SLE and 482 controls from Crete (OR 1.64, p=0.002; OR 1.43, p=0.002, respectively). Joint analysis of all patients with T1D (N=961) and all patients with SLE (N=1018) compared with 3976 healthy individuals yielded an allelic common OR of 1.19 (p=0.002) and 1.22 (p=2.6×10 −4 ), respectively. However, combining our dataset with the T1D sample set from the WTCCC resulted in a non-significant association (OR 1.06, p=0.087). In contrast, previously unpublished results from the SLEGEN study showed a significant association of the same allele (OR 1.19, p=0.0038) with an overall effect of 1.22 (p=1.02×10 −6 ) in a total of 1577 patients with SLE and 4215 healthy individuals. Conclusion: A significant association was found for the TRAF1-C5 locus in SLE, implying that this region lies in a pathway relevant to multiple autoimmune diseases.